EDUCATION SYSTEM OF GREAT BRITAIN - Хolmatova Oygul Sherzodbek qizi; Abdurakhmanov Turakhon Saydullayevich (TADQIQOTLAR, 2025)
Annotation:  This  article  explores  the  structure  and  characteristics  of  the education  system  in  Great  Britain.  It  outlines  the  key  stages  of  learning,  types  of schools, and the importance of academic and personal development. The article also highlights  the  unique  aspects  of  British  education  that  contribute  to  its  global reputation.